1994
DOI: 10.1152/ajpregu.1994.267.3.r619
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to hemorrhage during acute and chronic hypoxia

Abstract: Previous work from our laboratory had demonstrated attenuation of systemic vasoreactivity to pressor agents in rats after acute or chronic exposure to hypoxia. Therefore we hypothesized that hemorrhage of acutely hypoxic (12% O2) or chronically hypoxic (barometric pressure 380 mmHg for 3 wk) rats would deter the normal increase in total peripheral resistance (TPR) and thus decrease the ability to maintain blood pressure. Progressive hemorrhage (2% of blood volume per min) was performed under conditions of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Consistent with these changes in PCO 2 , arterial pH remained unchanged in E-IH animals during hypoxia, whereas H-IH animals became alkalotic during IH and pH remained elevated compared with E-IH during normoxic re-exposure. Although we did not measure blood gases in 2-wk CH rats, our laboratory has previously shown that 4-wk CH results in a greater PO 2 and reduced pH and PCO 2 under both normoxic and hypoxic conditions com-pared with control animals, reflecting hyperventilation and acid-base adjustments to CH (36). Whether similar acclimation occurs with long-term IH exposure remains to be determined.…”
Section: Discussionmentioning
confidence: 89%
“…Consistent with these changes in PCO 2 , arterial pH remained unchanged in E-IH animals during hypoxia, whereas H-IH animals became alkalotic during IH and pH remained elevated compared with E-IH during normoxic re-exposure. Although we did not measure blood gases in 2-wk CH rats, our laboratory has previously shown that 4-wk CH results in a greater PO 2 and reduced pH and PCO 2 under both normoxic and hypoxic conditions com-pared with control animals, reflecting hyperventilation and acid-base adjustments to CH (36). Whether similar acclimation occurs with long-term IH exposure remains to be determined.…”
Section: Discussionmentioning
confidence: 89%
“…Hypobaric and nitrogen dilution hypoxia have been used to generate pulmonary hypertension in rats. A continuous 3-week exposure of rats to a low F102 (10-12%, in nitrogen) with normobaria or to a simulated altitude of 16,000 ft (hypobaric chambers, PBar = -250 mmHg) results in progressive lung vascular muscularization and pulmonary hypertension (36,223,(234)(235)(236)(237)(238). Unlike the monocrotaline model, little if any pulmonary edema and inflammation are present in the established model (36,239,240).…”
Section: Hypoxia-induced Pulmonarymentioning
confidence: 99%
“…Acute hypoxia induces pulmonary hypertension through an increase in pulmonary arteriolar constriction, which causes resistance to blood flow through the lung. Erythropoietinmediated polycythemia follows with an increase of atrial natriuretic peptide (a cardiac hormone) in the blood (236,241). The hypoxia also stimulates production of vascular endothelial growth factor and expression of its receptor (223) as well as expression of fibronectin and laminin (220), interleukin-la (242), nitric oxide synthase (240), interleukin-6 (243), and endothelin (222), all of which are linked to vascular remodeling.…”
Section: Hypoxia-induced Pulmonarymentioning
confidence: 99%
“…Acute hypoxia induces pulmonary hypertension through an increase in pulmonary arteriolar constriction, which causes resistance to blood flow through the lung. Erythropoietinmediated polycythemia follows with an increase of atrial natriuretic peptide (a cardiac hormone) in the blood (236,241 Although the pathogenesis of the lesions is significantly different between the monocrotaline and hyopxia models, the lesions in each model result in functional pulmonary hypertension and vascular remodeling reminiscent of the idiopathic human disorder (36,37). Chronic hypoxia typically yields a largely reversible pulmonary hypertensive condition, whereas monocrotaline results in a progressive, irreversible, and frequently fatal disorder.…”
Section: Cardiopulmonary Vascular Diseasesmentioning
confidence: 99%